Analisis Kimia Kopi Cherry Arabika (Coffea arabica) dengan Kajian Kadar Alkohol, Kadar Kafein, Total Padatan Terlarut dan Total Asam Pada Limbah Hasil Fermentasi Anaerobik - Syahirman Hakim; Irwnsyah Irwnsyah; Risky Widayat; Baihaqi Baihaqi (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
This study aimed to determine the quantitative measurements of alcohol concentration, caffeine content, total dissolved solids, and total acid. This study used an experimental design with a non-factorial, Completely Randomized Design (CRD) that included three treatment levels, each replicated three times. The study consists of the following treatment levels: H5 represents the fermentation of cherry Arabica coffee for five days, H10 for ten days, and H15 for 15 days. The collected data underwent analysis of variance (ANOVA) using SPSS version 22. The Duncan's New Multiple Range Test (DNMRT) was used at a 5% significance level to determine the differences in the effects of each therapy. The study showed that the length of anaerobic fermentation of Arabica coffee cherries significantly affected the concentrations of alcohol, caffeine, total dissolved solids, and total acid (p<0.05). With longer fermentation, alcohol concentration, caffeine content, and total acid levels increase while the total dissolved solids content decreases. The most effective treatment in this study was noted on the 5th day of fermentation, showing an average alcohol content of 11.93%, caffeine content of 3.36%, total dissolved solids of 4.83oBrix, and total acid of 1.62%.